Analisis Kesalahan Berbahasa pada Surat Keluar di Kantor Desa Sihare’o I Tabaloho - Harefa, Esther Novi Christin; Zebua, Abdi Jevania; Mendrofa, Mei Siska Putri; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
This qualitative research aims to determine the type of Indonesian language errors found in the exit letter of the Sihare'o 1 Tabaloho Village Office. This study uses the manuscript of the exit letter of the Sihare'o 1 Tabaloho Village Office as a source of data. Data collection was carried out through observation and recording techniques, and data analysis was carried out through the listening method. The data analysis techniques used in this study are reduction and conclusion. The results of the analysis showed that there were several types of Indonesian language errors found in the letter issued by the Sihare'o 1 Tabaloho Village apparatus. These errors include capital errors, word errors, word separation errors, word usage errors, italics errors, and punctuation errors